Does using social media increase or decrease happiness? An empirical study of Facebook users in Taiwan - Lee, Ming‐Hsuan; Liu, Ya‐Ming; Yu, Clarence (Pacific economic review (Oxford, England), 2024)
In 2022, approximately 90% of the entire population in Taiwan actively used social media. Although several studies have examined emotional changes among social media users in Taiwan, the endogeneity problem stemming from reverse causality has not been recognized and properly addressed. Therefore, this study examines the effect of social media usage on negative emotions using ‘the frequency of using mobile phones as opposed to landline phones’ and ‘the frequency of using the Internet to run errands’ as instrumental variables for social media usage. Using data collected from the 2017 ‘Taiwan Social Change Survey’, our estimation results showed that Facebook usage significantly increased the frequency with which users experienced negative emotions, including envy, feelings of inferiority, and depression. The findings suggested that the negative emotions caused by social comparison via social media likely outweighed the happiness derived from social media, resulting in Facebook users experiencing more negative emotions. One important implication of our study is that reducing social media usage can alleviate mood swings.